A linear mathematical model to determine the minimum utility targets for a batch process - Chaturvedi, Nitin Dutt (Italian Association of Chemical Engineering - AIDIC, 2015)
This paper presents a mathematical model to determine the minimum utility targets for a batch process. The model was developed based on the source-demand classification of process streams where each stream was simultaneously treated as a source at its shifted supply temperature and as a demand at its shifted target temperature. The proposed model was formulated as a linear programming model (LP) and hence, guarantees the global optimal solution. The mathematical model can be used to calculate the utility targets for any fixed-schedule batch process. As the formulation is linear solutions, it can be guaranteed to be globally optimal. Applications of the proposed mathematical formulation on two illustrative examples demonstrate significant energy saving potential. Potential reductions of 52 % in hot utility and 48 % in cold utility have been estimated for the first example. Similarly, reductions of 71 % in hot utility and 65 % in cold utility can be potentially achieved for the second example.